Intensive Care Unit Cultures and End-of-Life Decision Making - Baggs, Judith Gedney (2007)
PURPOSE: Prior researchers studying end-of-life decision making (EOLDM) in intensive care units (ICUs) often have collected data retrospectively and aggregated data across units. There has been little research, however, about how cultures differ among ICUs. This research was designed to study limitation of treatment decision making in real time, to evaluate similarities and differences in the cultural contexts of four ICUs and the relationship of those contexts to EOLDM. MATERIALS AND METHODS: Ethnographic field work took place in four adult ICUs in a tertiary care hospital. Participants were health care providers (e.g., physicians, nurses, and social workers), patients and their family members. Participant observation and interviews took place 5 days/week for 7 months in each unit. RESULTS: The ICUs were not monolithic. There were similarities, but important differences in EOLDM were identified in formal and informal rules, meaning and uses of technology, physician roles and relationships, processes such as unit rounds, and timing of initiation of EOLDM. CONCLUSIONS: As interventions to improve EOLDM are developed, it will be important to understand how they may interact with unit cultures. Attempting to develop one intervention to be used in all ICUs is unlikely to be successful.